The Future of Work: Digital Leadership and Employee Wellbeing in Hybrid Organizations - Roy Darmawan; Sri Kiswati; Warsino Warsino; Ratna Kurnia Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the role of digital leadership in enhancing employee well-being within organizations that adopt hybrid work models, which have become increasingly prevalent due to the acceleration of digital transformation. Technology-based work environments require leaders to effectively manage virtual communication, digital workloads, and working conditions that influence employees’ psychological well-being. This study aims to analyze the effect of digital leadership on employee well-being while also evaluating the mediating role of digital working conditions. A quantitative method was employed, with data collected through an online survey of employees from various industrial sectors implementing hybrid work arrangements. The data were analyzed using a structural equation modeling approach. The results indicate that digital leadership has a direct positive effect on employee well-being and an indirect effect through the reduction of digital stressors such as information overload and task fragmentation. These findings highlight the importance of human-centered, adaptive leadership behaviors that are capable of balancing technological demands with employees’ psychological needs. The practical implications of this study underscore the need to develop digital leadership capacities to create a healthy and sustainable hybrid work ecosystem.